Iatrogenic Splenic Artery Pseudoaneurysm: Case Report and Review of Literature - Aesha M. Al Johani; Mostafa A. Al-Habboubi; Suzan M. Felemban; Abdulrahman A. Meccawy (Journal of King Abdulaziz University: Medical Sciences, 2023)
Splenic artery pseudoaneurysm is a known but uncommon complication of pancreatitis and a blunt abdominal trauma which can also be iatrogenic. A case study of a 58-year-old male who presented with epigastric pain and abdominal distension is reported. An initial ultrasound and computerized tomography showed a pseudocyst of the pancreas with the splenic artery passing through it. An attempt to do computerized tomography guided drainage of the cyst resulted in a rupture of the splenic artery inside the cyst. He was managed conservatively and discharged. Six months later, the patient came in with progressive distension of the abdomen. Endovascular embolization of splenic artery failed, thus, he was treated surgically. This case highlights the importance of a thorough evaluation of pseudocysts to identify any vessels in their cavity or wall, and that radiological aspiration of pseudopancreatic cyst should be done by senior, experienced radiologist.